2022
DOI: 10.25046/aj070107
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Generators (TEGs) and Thermoelectric Coolers (TECs) Modeling and Optimal Operation Points Investigation

Abstract: Sustainable energy is gradually becoming the norm today due to greenhouse warming effects; as a result, the quests for different renewable energy sources such as photovoltaic cells as well as energy efficient electrical appliances are becoming popular. Therefore, this article explores the alternative energy case for thermoelectricity with focus on the steadystate mathematics, mixed modelings and simulations of multiple TEGs and TECs modules to study their performance dynamics and to establish their optimal ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…To generate electricity, a TEG needs to be exposed to a temperature difference between the hot and cold sides. This temperature difference is due to heat transfer, and the rate of heat in watts absorbed by the hot side of a TEG [15,16] is given as:…”
Section: Assessing Teg Performancementioning
confidence: 99%
“…To generate electricity, a TEG needs to be exposed to a temperature difference between the hot and cold sides. This temperature difference is due to heat transfer, and the rate of heat in watts absorbed by the hot side of a TEG [15,16] is given as:…”
Section: Assessing Teg Performancementioning
confidence: 99%
“…In (Bayendang et al, 2022), thermoelectricity is proposed as an alternative energy source (TEG) as well as an energy-saving load (TEC) for many applications requiring low DC power, cooling, and heating. It has been found that the output current from the TEG or the input current to the TEC initially increases the TEG output power and the TEC cooling power, respectively.…”
Section: Introductionmentioning
confidence: 99%